PHENOMENOLOGY OF BODY IN THE CONTEXT OF POST-HUMANISM (ON THE EXAMPLE OF POPULAR SERIES IN THE GENRE OF CYBERPUNK) / ФЕНОМЕНОЛОГИЯ ТЕЛА В КОНТЕКСТЕ ПОСТГУМАНИЗМА (НА ПРИМЕРЕ ПОПУЛЯРНЫХ СЕРИАЛОВ ЖАНРА КИБЕРПАНК) - STROEVA OLESYA V. / СТРОЕВА ОЛЕСЯ ВИТАЛЬЕВНА (Наука телевидения, 2018)
The article is devoted to the phenomenology of the interaction of the body and consciousness in the context of the latest researches on artificial intelligence, correlated to the artistic images created by cinematography in the genre of cyberpunk. The category of the body as a philosophical issue has been formulated as the result of the influence of 20th century phenomenologists. Contemporary scholarly studies in Russia and in other countries aspire to synthesize philosophy, neurophysiology, psychology and cybernetics in order to analyze the constitution of subjectivity in the context of the growing trends of post-humanism. Comprehension of the relationship between the body and consciousness becomes even more relevant in the context of the impact of technology on modern society, as well as concerning the correlation of the real, virtual and artificial body. The creation of artificial intelligence, the development of biotechnology, the improvement of robots has ceased to be mere fiction, being gradually realized in practice and as a form of artistic expression and being realized in the genre of cyberpunk. Such popular television series as “Black Mirror” (2011), “Westworld” (2016), and “Philip C. Dick’s Electric Dreams (2017) and “Altered Carbon” (2018) offer futuristic assumptions of transformations in the relationship between consciousness and the body, and also present interesting material for phenomenological analysis of the formation of the image of “I” in the context of cyber-reality. The desire of man to animate matter, to create an artificial body endowed with self-consciousness, to create an artificial being according to his own image and likeness presents one of the key components of mimesis, which underlie human culture. The author argues that interdisciplinary approach in this matter would be conducive to approaching the understanding of the functioning of consciousness and self-awareness, as well as to human problems in the functioning of the transcendental sphere.